Evaluation on a mobile robotic software platform - Michael Sanjaya Wira. (2010)
Simultaenous Localization and Mapping (SLAM) is a technique used for an autonomous robot to create a map from an unknown environment by using landmarks and at the same time using the map to locate where the robot is located on the map. SLAM offers advantage in providing robot's position and orientation (pose) and where landmarks are located better than a GPS for indoor tasks or in constrained environment. SLAM -unlike GPS- does not rely on external equipments to do its localization rather it is using sensors placed on board. The development of SLAM performance will bring more opportunities to use robot for exploration or for search and rescue. Nowadays, numerous techniques of SLAM